2022
DOI: 10.1177/21501319221089767
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Diabetic Foot Ulcer Patients Pre- and During COVID-19 Pandemic: Lessons Learnt From a National Referral Hospital in Indonesia

Abstract: Background: Diabetic foot ulcer (DFU) is one of the most terrifying diabetic complications for patients, due to the high mortality rate and risk for amputation. During the COVID-19 pandemic, many diabetic patients limited their visits to the hospital, resulting in delays for treatment especially in emergency cases. Objective: This study aimed to compare the characteristics of patients with DFU pre- and during COVID-19 pandemic period. Methods: This study was a retrospective cohort study using foot registry dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
4
19
2
Order By: Relevance
“…In South India, a retrospective, single-centered study [ 48 ] showed a 54.1% increase in major amputations noted in the pandemic period compared to the pre-pandemic period. In Indonesia, in a retrospective study [ 49 ] conducted in a tertiary referral hospital, the authors found that the proportion of amputation was higher during the pandemic (39.3% vs. 56.3%) and the proportion of major amputation was almost twice as high during the pandemic than the pre-pandemic (20.2% vs. 39.4%). In Bangladesh, a retrospective single-center study [ 50 ] reported increased prevalence of total amputations as well as major and minor amputations during the pandemic period.…”
Section: The Indirect Impact Of the Covid-19 Pandemic On Diabetes-rel...mentioning
confidence: 99%
See 1 more Smart Citation
“…In South India, a retrospective, single-centered study [ 48 ] showed a 54.1% increase in major amputations noted in the pandemic period compared to the pre-pandemic period. In Indonesia, in a retrospective study [ 49 ] conducted in a tertiary referral hospital, the authors found that the proportion of amputation was higher during the pandemic (39.3% vs. 56.3%) and the proportion of major amputation was almost twice as high during the pandemic than the pre-pandemic (20.2% vs. 39.4%). In Bangladesh, a retrospective single-center study [ 50 ] reported increased prevalence of total amputations as well as major and minor amputations during the pandemic period.…”
Section: The Indirect Impact Of the Covid-19 Pandemic On Diabetes-rel...mentioning
confidence: 99%
“…The first reports during the lockdown were limited to small cohorts of single specialized centers which showed different results [24,39,40,43,[47][48][49][50][51][52], while subsequently several complete population studies have been published [42,[44][45][46]56].…”
Section: Conclusion and Lessons Learned For Our Futurementioning
confidence: 99%
“…Likewise, research needs to expand by getting more diverse and inclusive of a greater spectrum of socio-political landscapes. A good example of that is a recent study by Yunir et al [ 26 ] in Indonesia. We believe the conditions of the pandemic will inevitably contribute to the rapid development of the means of this method, either in the form of new software or patient and physician digital education and familiarization.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic posed major challenges in DFU care across the globe due the above reasons[ 9 - 11 ]. Delays in ulcer reviews may be associated with detrimental effects on DFU healing that may even lead to amputations[ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic posed major challenges in DFU care across the globe due the above reasons[ 9 - 11 ]. Delays in ulcer reviews may be associated with detrimental effects on DFU healing that may even lead to amputations[ 10 , 11 ]. Telephone and video clinics during the pandemic period helped clinicians to address some of the issues related to the inability of patients to attend medical clinics during the COVID-19 lock-down period.…”
Section: Introductionmentioning
confidence: 99%